Non-Control-Data Attacks Are Realistic Threats - Chen, Shuo; Xu, Jun; Sezer, Emre C.; Gauriar, Prachi; Iyer, Ravishankar K. (Proceedings of USENIX Security Symposium, 2005)
Most memory corruption attacks and Internet worms follow a familiar pattern known as the control-data attack. Hence, many defensive techniques are designed to protect program control flow integrity. Although earlier work did suggest the existence of attacks that do not alter control flow, such attacks are generally believed to be rare against real-world software. The key contribution of this paper is to show that non-control-data attacks are realistic. We demonstrate that many real-world applications, including FTP, SSH, Telnet, and HTTP servers, are vulnerable to such attacks. In each case, the generated attack results in a security compromise equivalent to that due to the controldata attack exploiting the same security bug. Non-control-data attacks corrupt a variety of application data including user identity data, configuration data, user input data, and decision-making data. The success of these attacks and the variety of applications and target data suggest that potential attack patterns are diverse. Attackers are currently focused on control-data attacks, but it is clear that when control flow protection techniques shut them down, they have incentives to study and employ non-control-data attacks. This paper emphasizes the importance of future research efforts to address this realistic threat.
Source code of attack programs can be obtained from the attached txt file.